2016
DOI: 10.1177/0305735616628659
|View full text |Cite
|
Sign up to set email alerts
|

Achievement motivation for band: A cross-cultural examination of the 2 × 2 achievement goal motivation framework

Abstract: The purpose of this study was to explore the achievement goal motivation orientations of instrumental music students in the US and Singapore. Participants in this study were volunteer band students ( N = 359) from eight American public high schools ( n = 217) and five polytechnics in Singapore ( n = 142). Data were collected via a questionnaire that included measures of (a) the 2 × 2 achievement goal orientation constructs (mastery approach, mastery avoid, performance approach, and performance avoid), (b) flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 67 publications
5
30
1
1
Order By: Relevance
“…Miksza (2009a) examined the validity of the 2 × 2 achievement goal model using self-report data from secondary instrumental students. In line with research conducted in academic and sports settings (Elliot & McGregor, 2001;Elliot & Murayama, 2008;Wang, Biddle, & Elliot, 2007), confirmatory factor analyses indicated that when compared with competing dichotomous and trichotomous models, the 2 × 2 achievement goal model was the best relative fit to the data, a finding replicated in a follow-up study (Miksza, Tan, & Dye, 2016). In both studies, fair amounts of covariance were detected between the approach and avoidance dimensions of both mastery and performance constructs.…”
Section: Music Research In Achievement Goal Theorysupporting
confidence: 71%
“…Miksza (2009a) examined the validity of the 2 × 2 achievement goal model using self-report data from secondary instrumental students. In line with research conducted in academic and sports settings (Elliot & McGregor, 2001;Elliot & Murayama, 2008;Wang, Biddle, & Elliot, 2007), confirmatory factor analyses indicated that when compared with competing dichotomous and trichotomous models, the 2 × 2 achievement goal model was the best relative fit to the data, a finding replicated in a follow-up study (Miksza, Tan, & Dye, 2016). In both studies, fair amounts of covariance were detected between the approach and avoidance dimensions of both mastery and performance constructs.…”
Section: Music Research In Achievement Goal Theorysupporting
confidence: 71%
“…On the whole, the individual item scores of the Singapore participants appeared higher than those of their US counterparts. These findings stand in contrast to a line of Singapore-US cross-cultural research in music education which found no significant differences among instrumental students' achievement goal orientations toward band (Miksza, Tan and Dye, 2016;Tan & Miksza, 2018), and little differences among general music teachers' pedagogical creativity (Abramo & Tan, 2017). Given that Asians are in general less likely to indicate extreme scores in Likert-type scales (Chen, Lee and Stevenson, 1995), the higher scores reported in this study suggest some possible avenues for fruitful comparisons in music teacher education between the two countries.…”
Section: Generalcontrasting
confidence: 99%
“…Some achievement motivation research has suggested that individuals in Eastern countries such as Japan, South Korea, and China, are more avoidance-oriented, focus more on the process of improvement than on outcomes per se , and desire to fit in rather than stand out (Dekker and Fischer, 2008 ; Heine, 2008 ; Elliot et al, 2012 ; King and McInnerney, 2014 ). It would be interesting to extend research on the 2 × 2 standpoints model to these countries and to conduct cross-cultural comparisons of the prevalence and implications of adopting these goals in different cultural contexts (for related work using the 2 × 2 standards model, see King, 2015 ; Miksza et al, 2016 ; Poondej and Lerdpornkulrat, 2016 ). Another limitation is that we focused only on the predictive utility of goal pursuit and did not examine antecedents of goal adoption.…”
Section: Discussionmentioning
confidence: 99%